Microtubule Formation and Activities of Antioxidative Enzymes in PC12 Cells Exposed to Phosphatidylcholine Hydroperoxides - Yukako Yamanaka (International Journal of Molecular Sciences, 2012)
Aging increases free radical generation and lipid oxidation and, thereby, mediates neurodegenerative diseases. As the brain is rich in lipids (polyunsaturated fatty acids), the antioxidative system plays an important role in protecting brain tissues from oxidative injury. The changes in microtubule formation and antioxidative enzyme activities have been investigated in rat pheochromocytoma PC12 cells exposed to various concentrations of phosphatidylcholine hydroperoxides (PCOOH). We measured three typical antioxidative enzymes, superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase (CAT). The microtubule assembly system was dependent on the antioxidative enzyme system in cells exposed to oxidative stress. The activities of the three enzymes increased in a PCOOH exposure-dependent manner. In particular, the changes in the activity as a result of PCOOH exposure were similar in the three antioxidative enzymes. This is the first report indicating the compatibility between the tubulin-microtubule and antioxidative enzyme systems in cells that deteriorate as a result of phospholipid hydroperoxide administration from an exterior source. The descending order of sensitivity of the three enzymes to PCOOH is also discussed.